Educational policy or practice? Traversing the conceptual divide between subject knowledge, pedagogy and teacher identity in England - Woolhouse, Clare; Cochrane, Matt (European journal of teacher education, 2015)
This research paper is framed by concerns about recent UK Government policy regarding the training of mathematics and science teachers in England and discusses how two cohorts of pre-service teachers negotiated the development of a professional identity while undertaking subject-specific training. The data reported upon were garnered in two ways; through an evaluation survey that received quantitative and qualitative responses from 159 teacher trainees and through focus groups conducted with 40 trainees. In the paper, the authors take the concept of 'participation in communities of practice' as a departure point to explore how trainees demonstrate their development of professional identities as chemistry, maths or physics teachers. In the conclusion, the authors consider the implications of the findings for pre-service teachers and teacher trainers given the current education climate of financial austerity being experienced across Europe.